Gold nanoparticles cellular toxicity and recovery: Adipose Derived Stromal cells. Issue 2 (March 2014) - Mironava, Tatsiana; Hadjiargyrou, Michael; Simon, Marcia; Rafailovich, Miriam H.
Abstract Gold nanoparticles (AuNPs) are currently used in numerous medical applications. Herein, we describe their in vitro impact on human adipose-derived stromal cells (ADSCs) using 13 nm and 45 nm citrate-coated AuNPs. In their non-differentiated state, ADSCs were penetrated by the AuNPs and stored in vacuoles. The presence of the AuNPs in ADSCs resulted in increased population doubling times, decreased cell motility and cell-mediated collagen contraction. The degree to which the cells were impacted was a function of particle concentration, where the smaller particles required a sevenfold higher concentration to have the same effect as the larger ones. Furthermore, AuNPs reduced adipogenesis as measured by lipid droplet accumulation and adiponectin secretion. These effects correlated with transient increases in DLK1 and with relative reductions in fibronectin. Upon removal of exogenous AuNPs, cellular NP levels decreased and normal ADSC functions were restored. As adiponectin helps regulate energy metabolism, local fluctuations triggered by AuNPs can lead to systemic changes. Hence, careful choice of size, concentration and clinical application duration of AuNPs is warranted.